Entrepreneurship: Cause and Consequence of Financial Optimism. Issue 4 (December 2014) - Dawson, Christopher; de Meza, David; Henley, Andrew; Arabsheibani, G. Reza
<x xml:space="preserve">Abstract</x> Extant evidence that the self‐employed overestimate their returns by a greater margin than employees is consistent with two mutually inclusive possibilities. Self‐employment may foster optimism or intrinsic optimists may be drawn to self‐employment. Previous research is generally unable to disentangle these effects because of reliance on cross‐sectional data. Using longitudinal data, this paper finds that employees who will be self‐employed in the future overestimate their short‐term financial wellbeing by more than those who never become self‐employed. Optimism is higher still when self‐employed. These results suggest that the greater optimism of the self‐employed reflects both psychological disposition and environmental factors. By providing greater scope for optimism, self‐employment entices the intrinsically optimistic.